A phytochemical and pharmacological study of acalypha wilkesiana var. macafeana hort. (euphorbiaceae juss.): antioxidant and antibacterial analyses - Mustafa Din, Wardah (2014)
A tropical shrub from Euphorbiaceae (Juss.) family, namely Acalypha wilkesiana var. macafeana hort. was investigated for its antioxidant and antibacterial properties. The antioxidant properties were assayed by Ferric Reducing Antioxidant Power (FRAP) assay, 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay and β-carotene bleaching assay. Assessment of its antibacterial properties was conducted with pour plate disc diffusion assay and dilution methods. The plant was collected, dried, grinded and soaked continuously in four different solvent starting from non-polar to polar solvent: hexane, ethyl acetate, ethanol and water. The crude extracts were concentrated under pressure and kept in -20 °C prior to investigation.